Pharmacological inhibition of CDK4/6 impairs diffuse pleural mesothelioma 3D spheroid growth and reduces viability of cisplatin-resistant cells - Costa, Aurora; Forte, Iris Maria; Pentimalli, Francesca; Iannuzzi, Carmelina Antonella; Alfano, Luigi; Capone, Francesca; Camerlingo, Rosa; Calabrese, Alessandra; von Arx, Claudia; Benot Dominguez, Reyes; Quintiliani, Massimiliano; De Laurentiis, Michelino; et al. (Frontiers in Oncology, 2024)
Introduction Diffuse pleural mesothelioma (DPM) of the pleura is a highly aggressive and treatment-resistant cancer linked to asbestos exposure. Despite multimodal treatment, the prognosis for DPM patients remains very poor, with an average survival of 2 years from diagnosis. Cisplatin, a platinum-based chemotherapy drug, is commonly used in the treatment of DPM. However, the development of resistance to cisplatin significantly limits its effectiveness, highlighting the urgent need for alternative therapeutic strategies. New selective inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6) have shown promise in various malignancies by inhibiting cell cycle progression and suppressing tumor growth. Recent studies have indicated the potential of abemaciclib for DPM therapy, and a phase II clinical trial has shown preliminary encouraging results. Methods Here, we tested abemaciclib, palbociclib, and ribociclib on a panel of DPM cell lines and non-tumor mesothelial(MET-5A) cells. Results Specifically, we focused on abemaciclib, which was the mosteffective cytotoxic agent on all the DPM cell lines tested. Abemaciclib reduced DPM cell viability, clonogenic potential, and ability to grow as three-dimensional (3D) spheroids. In addition, abemaciclib induced prolonged effects, thereby impairing second-generation sphere formation and inducing G0/G1 arrest and apoptosis/ necrosis. Interestingly, single silencing of RB family members did not impair cell response to abemaciclib, suggesting that they likely complement each other in triggering abemaciclib’s cytostatic effect. Interestingly, abemaciclib reduced the phosphorylation of AKT, which is hyperactive in DPM and synergized with the pharmacological AKT inhibitor (AKTi VIII). Abemaciclib also synergized with cisplatin and reduced the viability of DPM cells with acquired resistance to cisplatin. Discussion Overall, our results suggest that CDK4/6 inhibitors alone or in combination with standard of care should be further explored for DPM therapy.